Aging rather than stress strongly influences amino acid metabolisms in the brain and genital organs of female mice. (March 2017) - Kodaira, Momoko; Nagasawa, Mao; Yamaguchi, Takeshi; Ikeda, Hiromi; Minaminaka, Kimie; Chowdhury, Vishwajit S.; Yasuo, Shinobu; Furuse, Mitsuhiro
Highlights: Middle-aged mice were susceptible to stress in terms of body-weight loss. Emotional behavior did not differ between young mice and middle-aged mice. Amino acid metabolisms in the brain and genital organs were affected by aging. Abstract: Aging and stress affect quality of life, and proper nourishment is one of means of preventing this effect. Today, there is a focus on the amount of protein consumed by elderly people; however, changes in the amino acid metabolism of individuals have not been fully considered. In addition, the difference between average life span and healthy life years is larger in females than it is in males. To prolong the healthy life years of females, in the present study we evaluated the influence of stress and aging on metabolism and emotional behavior by comparing young and middle-aged female mice. After 28 consecutive days of immobilization stress, behavioral tests were conducted and tissue sampling was performed. The results showed that the body weight of middle-aged mice was severely lowered by stress, but emotional behaviors were hardly influenced by either aging or stress. Aging influenced changes in amino acid metabolism in the brain and increased various amino acid levels in the uterus and ovary. In conclusion, we found that aged mice were more susceptible to stress in terms of body-weight reduction, and that amino acid metabolisms in the brain and genital organs were largely influenced by aging rather than by stress.